2002
DOI: 10.1091/mbc.01-06-0308
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Pore Complex Is Able to Transport Macromolecules with Diameters of ∼39 nm

Abstract: Bidirectional transport of macromolecules between the nucleus and the cytoplasm occurs through the nuclear pore complexes (NPCs) by a signal-mediated mechanism that is directed by targeting signals (NLSs) residing on the transported molecules or "cargoes." Nuclear transport starts after interaction of the targeting signal with soluble cellular receptors. After the formation of the cargo-receptor complex in the cytosol, this complex crosses the NPC. Herein, we use gold particles of various sizes coated with car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
535
2
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 725 publications
(578 citation statements)
references
References 36 publications
31
535
2
10
Order By: Relevance
“…Although electron microscopy studies have shown that the NPC could expand to accommodate the longitudinal passage of the 30S proteasome, the permeability barriers towards macromolecules such as CP precursor complexes and RP assembly modules must be overcome by specific importins/karyopherins ( Pante & Kann, 2002). Several classical NLSs exist within the N-termini of distinct α subunits which were proposed to be either accessible rendering the CP in an import-competent conformation, or to be masked rendering the CP in an import-incompatible conformation ( Tanaka et al , 1990).…”
Section: Discussion/analysis Of the Literaturementioning
confidence: 99%
“…Although electron microscopy studies have shown that the NPC could expand to accommodate the longitudinal passage of the 30S proteasome, the permeability barriers towards macromolecules such as CP precursor complexes and RP assembly modules must be overcome by specific importins/karyopherins ( Pante & Kann, 2002). Several classical NLSs exist within the N-termini of distinct α subunits which were proposed to be either accessible rendering the CP in an import-competent conformation, or to be masked rendering the CP in an import-incompatible conformation ( Tanaka et al , 1990).…”
Section: Discussion/analysis Of the Literaturementioning
confidence: 99%
“…Measurements of nuclear pore diameter range from 26 to 40 nm, with an outer diameter of 100-120 nm. [24][25][26] Oligonucleotides smaller than 68-mers have been shown to rapidly accumulate in the nucleus. 27 Previous work has revealed intracellular degradation of plasmid into oligonucleotides.…”
Section: Discussion Plasmid Translocation Rates In the Hela Cellsmentioning
confidence: 99%
“…Thereafter, preformed viral capsids are packaged with genomic DNA and have to be transported to the cytoplasm for final maturation and viral release. Due to the large size of cytomegaloviral capsids (~130 nm; Chen et al, 1999), these cannot be transported through the nuclear pore complex (~40 nm; Panté & Kann, 2002). The most widely accepted model for nuclear egress of HCMV and other herpesviruses is based on a transient primary envelopment by budding through the inner nuclear membrane (Mettenleiter, 2004(Mettenleiter, , 2006Sanchez & Spector, 2002;Sampaio et al, 2005).…”
Section: Introductionmentioning
confidence: 99%